<em>x = - 2</em>
<em>y = 5</em>
- <em>Step-by-step explanation:</em>
<em>Hi there ! </em>
<em>2x + 9 = y</em>
<em>y = - 4x - 3</em>
<em>
</em>
<em>equality</em>
<em>2x + 9 = - 4x - 3</em>
<em>2x + 4x = - 9 - 3</em>
<em>6x = - 12</em>
<em>x = - 12 : 6</em>
<em>x = - 2</em>
<em>replace x = - 2</em>
<em>2(-2) + 9 = y</em>
<em>- 4 + 9 = y</em>
<em>y = 5</em>
<em>Good luck !</em>
<em />
<em />
Answer:
Step-by-step explanation:
The graph shows the solution (-6,2)
i.e at x= -6 y=2
Analysis of each of the answers, since we can't write the equation of a straight line with only that information i.e the single point
Then,
Option 1
1. 2x - 3y = -6
x= -6 y=2
Then let insert x=-6 and y =2
2(-6)-3(2)
-12-6
-18.
Since -18 ≠ -6, then this is not the equation of the line and doesn't make up the system
Option 2
2. 4x - y = 26
Inserting x=-6 and y=2
4(-6)-(2)
-24-2
-26
Since -26 ≠ 26, then this is not the equation of the line and doesn't make up the system
Option 3
3. 3x + 2y = -14
Inserting x=-6 and y=2
3(-6)+2(2)
-18+4
-14
Since -14 ≠ -14 then this is the equation of the line and it make up the system.
Option 4
x-y = -2
Inserting x=-6 and y=2
(-6)-(2)
-6-2
-8
Since -8≠ -2, then this is not the equation of the line and doesn't make up the system
Option 5
5. x+y=-4
Inserting x=-6 and y=2
(-6)+(2)
-6+2
-4
Since -4 ≠ -4, then this is the equation of the line and it makes up the system.
Then, there are two option that make up the system
3. 3x + 2y = -14
And
5. x+y=-4
Let n be a number of friends at the perty. If <span>dinner costs $30 per person, then it cost $30n for all friends.
</span>
Robert has booked a banquet hall which costs <span>$200, then his total expenses are $200+30n.
</span>
If the final bill is p, then p=<span>200+30n.
</span>
Answer: p=<span>200+30n.</span>
-4 and 2 are the solutions, since that is where they intercept the x axis, and when plugged into the equation, make it true.
Answer:
1/6
Step-by-step explanation:
Let
c-----> the number of cola bottles that Dan picks
s ----> the number of smarties that Dan picks
m ---> the number of marshmallows that Dan picks
we know that
c=3s ----> equation A
m=2s ---> equation B
we know that
To find out the proportion of the bag of sweets that are smarties, divide the number of smarties by the total of sweets
The total of sweets is equal to
(c+s+m)
substitute equation A and equation B in the total of sweets
(3s+s+2s) =6s
Find the proportion
s/6s
Simplify
1/6